Kekerasan struktural dalam novel Laut Bercerita karya Leila S Chudori: Perspektif Johan Galtung - Arroyan, Bunga Muzdholifah (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is to analyze the structural violence in Leila S. Chudri’s novel "Laut Bercelita" from the perspective of Johan Galtung. This study used a qualitative descriptive method using a literature review as the data collection method. The primary data source is in the form of the novel “Following Berselita” by Leila S. Chudori. Data analysis techniques using reading and note-taking techniques. The theory used in the analysis is Johann Galtung’s theory of structural violence by observing the conflicts contained in the novel. The results of this study point to some disparities in the way governments act and the different forms of violence faced by their citizens.